Sustainable Management of Wild Chili (Capsicum annuum L. var. glabriusculum) as an Alternative from Production to the Northeast of Mexico - Villalon-Mendoza, Horacio; Ramirez-Meraz, Moises; Ocanas, Fortunato Garza; Maiti, R. K.; Luna-Ruiz, Jose de Jesus (International Journal of Bio-resource and Stress Management, 2015)
Mexico offers a wide range of cultivated varieties of chills, as well as wild chilies. This are considered as the ancestors of peppers Capsicum annuum, which are grown worldwide. In northeastern Mexico this wild chili is strongly rooted in its cuisine. Though this wild chili has high potential for production, the main problem is associated with the difficulty of seed germination for field production. A protocol of germination of piquin chili has been development with good germination. The increasing demand of the wild chili in the Northeast of Mexico and in the international markets, it has become necessary to find an alternative to in situ conservation and production in a sustainable way ex situ in its natural habitat in the Northeast of Mexico. The prices of this wild chili prices in northeastern Mexico in the market depend largely on prevailing climatic conditions in each season. Therefore, research efforts are undertaken in the development of technology for the management of wild chili production as a sustainable alternative for rural population. On the basis of the information generated on the sustainable management of the resource wild chili by the rural farmers, few technological packages have been developed through courses and workshops which are transferred to the farmers involved in the value chain of the wild chili of northeastern Mexico. Thereby, it has been possible for the effective management of the wild chili agro-forestry system as an alternative sustainable productivity (ecologically, economic, socially and technically viable ) in the northeast of Mexico.